Pengaruh Financial Stability, Nature Of Industry, Dan Change In Auditor Terhadap Financial Statements Fraud - Inday Hardika; Najwa Balqis; Nera Marinda Machdar (Universitas 45 Surabaya, 2024)
Fraud is an illegal activity that harms the company and benefits the perpetrator. According to the understanding of many experts, fraud refers to intentional misrepresentation for a specific purpose. Original research or studies on important scientific research or topics. Basic research or research activities involve verifying ideas and facts that show relationships or influences between variables. This article examines the factors that influence Financial Statements Fraud: Financial Stability, Nature of Industry, and Change in Auditors, which is a study of investigative audit literature. The purpose of writing this article is to create a hypothesis that will be used in further research regarding the influence between variables. The findings from this literature review are: 1) Financial Stability influences Financial Statements Fraud, 2) Nature of Industry influences Financial Statements Fraud, and 3) Change in Auditor influences Financial Statements Fraud.